EXPLORING THE ADVANTAGES OF CRITICAL READING STRATEGIES IN UNDERGRADUATE THESIS PROPOSAL DEVELOPMENT - Talitha Ayu Ramadhani; Nugroho, Him'mawan Adi; Widyastuti (Universitas Negeri Surabaya, 2024)
This study explores the advantages of critical reading strategies in the development of undergraduate thesis proposals. Using a qualitative research approach, six undergraduate students from a university in Surabaya were interviewed to gather insights into their experiences. The findings reveal that critical reading strategies play a significant role in supporting students throughout the thesis proposal writing process. Participants reported that these strategies help them understand and evaluate articles for use as sources, sort relevant citations, formulate hypotheses, and draft well-structured proposals. Additionally, critical reading strategies assist students in avoiding plagiarism, compiling literature reviews, drafting the background of the study, and identifying research gaps and questions. Students also noted that employing these strategies enhanced the quality of their proposals, making their work more efficient and effective. These findings highlight the importance of critical reading strategies in academic writing and suggest their potential for improving students’ overall research competencies.